Impacts of climate extremes on agriculture in Southern Africa - Chemura, A.; Gleixner, S.; Mkuhlani, S.; Kutywayo, D.; Nelson, A. (Elsevier, 2025)
Agriculture, particularly crop production, faces risks from the impacts of climate extremes. This risk is very high in Southern Africa where much of the agriculture is rainfed. An understanding of the trends and impacts of climate extremes is imperative for building resilient agri-food systems in the region and beyond. This chapter describes key climate systems affecting the climate of Southern Africa, major cropping systems, and the vulnerability of crop production to climate extremes in the region. Further, observational trends in selected temperature and precipitation-based climate extreme indices for cropland areas in the region during the growing season (October–May) for the period 1982–2019 are presented. The impacts that climate extremes present on crop production in the region, with a focus on cereals, root, and tuber crops, legumes, and tree crops, are discussed based on the observed trends. Major impacts are related to plant water balance at leaf and canopy levels from both increasing heat extremes and reduced water availability. This impacts crop yield, suitability, produce quality, nutrient content, and other aspects of the agricultural value chain. These impacts vary depending on crop type and the geographic area. It is therefore suggested that enhanced use of climate and weather information, crop improvement programs, crop diversification, and nature-based solutions can help build the resilience of crop production systems to climate extremes.